Real-Time Optimal Negotiation Mode Selection Based on Three-Way Decision for Decentralized Remote Sensing Satellite Cluster - Xuelei Deng; Yunfeng Dong; Chao Zhang (International Journal of Aerospace Engineering)
The mission planning for multisatellite is a complex optimization problem, which is sensitive to time delay caused by communication and decision. Different modes are suitable for different situations. Therefore, we design the workflows of three modes: the independence mode, the MAS mode, and the ground-based mode. And then, a real-time mode selection method based on the three-way decision is proposed to choose the best mode onboard. The experiments proved the effectiveness and advantage of our proposed method.